1993
DOI: 10.1111/j.1365-2621.1993.tb01296.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dough ingredients on apparent viscosity and properties of extrudates in twin‐screw extrusion‐cooking

Abstract: A capillary-type viscometer was used in a twin-screw extruder to measure the apparent viscosity of cooked-extruded wheat-flour dough with various ingredients: lecithin, palm oil, sucrose, whey, sodium chloride, and bran. The effects of concentration of these ingredients on dough rheology and physical properties of extrudates (apparent density, expansion ratios, mechanical, and crispness properties) were measured. The role of ingredients was discussed in terms of their physico-chemical effect on biopolymer conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 8 publications
(5 reference statements)
1
9
0
1
Order By: Relevance
“…Ralet et al [44] reported that wheat bran increased its water uptake after extrusion. This could be as a result of the disruption of covalent or non-covalent bonds in the carbohydrate and protein moieties, leading to smaller, more soluble molecular fragments [45,46]. These observations confirm similar findings reported for starch-based extrudates obtained either using single or twin screw extrusion [47,48].…”
Section: Water Solubility Index Y Wsisupporting
confidence: 81%
“…Ralet et al [44] reported that wheat bran increased its water uptake after extrusion. This could be as a result of the disruption of covalent or non-covalent bonds in the carbohydrate and protein moieties, leading to smaller, more soluble molecular fragments [45,46]. These observations confirm similar findings reported for starch-based extrudates obtained either using single or twin screw extrusion [47,48].…”
Section: Water Solubility Index Y Wsisupporting
confidence: 81%
“…Only few studies investigated the effect of wheat bran on the shear viscosity of extruded starchy melts. Moore et al (1990) and Wang et al (1993), using a capillary rheometer, reported no change in the apparent viscosity of cooked dough supplemented with up to 16% of wheat bran. However, the composition of the bran was not specified and the effect of bran on the flow behavior was not characterized.…”
Section: Introductionmentioning
confidence: 95%
“…However, its valorization in extruded food products is constrained due to its negative effect on product expansion and organoleptic properties (e.g. Wang et al, 1993;Brennan et al, 2008). Several works reported a decreasing effect of wheat bran on the expansion properties of starchy foams (Breen et al, 1977;Hsieh et al, 1989;Moore et al, 1990;Wang et al, 1993;Yanniotis et al, 2007;Brennan et al, 2008).…”
Section: Introductionmentioning
confidence: 96%
“…Supplementation of extruded products with wheat bran is a cost‐efficient way of increasing their dietary fiber content. However, wheat bran/fibers addition was reported to decrease expansion and increase the bulk density of extruded food foams (Breen and others 1977; Hsieh and others 1989; Moore and others 1990; Wang and others 1993; Yanniotis and others 2007; Brennan and others 2008). The reduced diameter, increased bulk density, and/or change in cellular structure characteristics resulting from the addition of wheat bran lead to harder textures (Wang and others 1993; Yanniotis and others 2007; Brennan and others 2008), less preferred by consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Only few works investigated the effect of bran on the melt rheological properties (Moore and others 1990; Wang and others 1993). In relevant studies, the shear viscosity was assessed using an online slit viscometer.…”
Section: Introductionmentioning
confidence: 99%